Penggunaan Analytical Hierarchy Process (AHP) Untuk Pemilihan Supplier Bahan Baku - Khairun Nisa, Addien Agustina; Subiyanto, Subiyanto; Sukamta, Sri (JSINBIS (Jurnal Sistem Informasi Bisnis), 2019)
The purpose of this paper is to present a decision support system supplier selection of food industry raw materials especially cake and bakery, by using new technology that is famous for its robustness that is Analytical Hierarchy Process (AHP). The importance of this research is to find a new varian of the AHP application, therefore increase scientific literature related the method especially for cake and bakery industrial. Furthemore, to provide a reference of selecting raw materials supplier methods in the industry. The model starts by identifying the main criteria (quality, price, delivery, and service) using the main criteria ranking based on the opinions of experts using AHP. The second stage is identifying the sub criteria (materials supplied halal and equipped with halal certificates, sample tests and physical observations, price of goods, maximum and continuous capacity and supply capacity, discount price levels and certain purchases, the existence of supplier offices and cooperation and reference commitments) and their ranking based on the main criteria. The results of this study indicate that the Analytical Hierarchy Process (AHP) method can produce a decision support system that the right results according to field data at Virgin Cake and Bakery. The results of this study indicate that overall the best supplier to be chosen by the company to be use as a long-term co-worker is supplier A because overall this supplier has the highest value compared to the other three suppliers.